High-performance flexible hybrid supercapacitor based on NiAl layered double hydroxide as a positive electrode and nitrogen-doped reduced graphene oxide as a negative electrode. (10th September 2020) - Li, Min; Dolci, Mathias; Roussel, Pascal; Barras, Alexandre; Szunerits, Sabine; Boukherroub, Rabah
Abstract: Herein, we investigated the influence of Fe, Cr and Al incorporation in Ni-based layered double hydroxides (LDHs) supported on nickel foam (NF) electrodes, prepared through a one-step hydrothermal, on their electrochemical performance. The resulting NiFe, NiCr and NiAl (LDHs) were further coated on carbon spheres (CS) supported on NF using a facile two-step hydrothermal process to produce NiFe LDHs@CS/NF, NiCr LDHs@CS/NF and NiAl LDHs@CS/NF. The performance of the prepared materials as binder-free electrodes in supercapacitors was assessed. Among all the prepared electrodes, NiAl LDHs@CS/NF electrode material achieved the largest areal capacity (1042.2 mC cm −2 at 1 mA cm −2 ), as compared to the areal capacity values attained by NiFe LDHs@CS/NF (705.8 mC cm −2 ) and NiCr LDHs@CS/NF (814.9 mC cm −2 ) at 1 mA cm −2 . Therefore, a hybrid supercapacitor device comprising NiAl LDHs@CS/NF as the positive electrode and N-doped reduced graphene/NF as the negative electrode was successfully fabricated. The device exhibited favorable flexibility, good mechanical properties and stability; the areal capacity remained ∼75% and ∼67% of the original value after 5000 and 10, 000 cycles, respectively. The hybrid supercapacitor attained an energy density of 43 μWh cm −2  at a power density of 0.805 mW cm −2 and was applied successfully to operate a home-made windmill device continuously for 32 s. Moreover, two flexible NiAl LDHs@CS/NF//N-rGO/NF hybrid supercapacitors, connected in series, were able to light up a green, a red and a yellow LED in parallel, lasting for 37 s, 542 s and 199 s, respectively, indicating their potential application for flexible energy storage devices. Highlights: NiAl LDH decorated on carbon spheres supported on Ni foam was prepared. The electrode material exhibited a high areal capacity of 1042.2 mC cm −2 at 1 mA cm −2 A supercapacitor was assembled and exhibited a high energy density of 43 μWh cm −2  at a power density of 0.805 mW cm −2 The supercapacitor was able to operate a home-designed windmill device for 32 s. The supercapacitor was used to light up a green, a red and a yellow LED.